2008
DOI: 10.1243/09544070jauto685
|View full text |Cite
|
Sign up to set email alerts
|

Cooling system improvements — assessing the effects on emissions and fuel economy

Abstract: The work reported in this paper details an experimental study of the effects of cooling system hardware changes on diesel engine emissions and fuel economy. Experiments were performed under both steady state and transient conditions and complemented by statistical assessments. Techniques for assessing the thermal integrity of the engine as a consequence of such changes are also presented. An experimental design was constructed to investigate the effect of water pump throttling, coolant flow control through the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 14 publications
2
22
0
Order By: Relevance
“…They also pointed out the complexity of and the lack of comprehensive studies on thermal effects on combustion. Brace et al 8 tested several cooling system modifications and showed a fuel economy benefit of around 2%, accompanied by an NOx penalty between 12% and 45% under steady operating conditions. Smaller effects were observed in the driving cycle (a 0.4% fuel economy benefit and a 10% NOx increase).…”
Section: Introductionmentioning
confidence: 99%
“…They also pointed out the complexity of and the lack of comprehensive studies on thermal effects on combustion. Brace et al 8 tested several cooling system modifications and showed a fuel economy benefit of around 2%, accompanied by an NOx penalty between 12% and 45% under steady operating conditions. Smaller effects were observed in the driving cycle (a 0.4% fuel economy benefit and a 10% NOx increase).…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of the cooling system coolant was recorded during an urban driving cycle for both upper and lower radiator tanks (down flow radiator). The results showed significant differences between the two readings, as described in detail in ref [14].…”
Section: Experimental Apparatusmentioning
confidence: 57%
“…This component is also a wax element device but is sensitive to both the top-hose coolant temperature and the bottom-hose coolant temperature, meaning that it can react to the cooling potential over the radiator. 8 The active TMS included the following:…”
Section: Methodsmentioning
confidence: 99%
“…Some active systems are only beneficial under fully warm conditions and do not offer any benefits during warm-up because they do not change the available energy per unit thermal mass. [7][8][9] To achieve benefits during warm-up, either reduced inertia or heat addition must occur. 6 Careful placing of coolant control valves can improve the engine behaviour during warm-up by isolating parts of the circuit and effectively reducing the thermal inertia during warm-up.…”
Section: Introductionmentioning
confidence: 99%